1997
DOI: 10.1103/physrevb.56.8542
|View full text |Cite
|
Sign up to set email alerts
|

Environment-dependent interatomic potential for bulk silicon

Abstract: We use recent theoretical advances to develop a new functional form for interatomic forces in bulk silicon. The theoretical results underlying the model include a novel analysis of elastic properties for the diamond and graphitic structures and inversions of ab initio cohesive energy curves. The interaction model includes two-body and three-body terms which depend on the local atomic environment through an effective coordination number. This formulation is able to capture successfully: (i) the energetics and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
242
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(250 citation statements)
references
References 54 publications
4
242
0
4
Order By: Relevance
“…Because this method is computationally expensive for large targets, we first constructed a smaller 10×10×10 nm 3 block, and then copied it four times to achieve the desired size. The resulting composite was then annealed with the environment-dependent interatomic potential 32 . This gives an optimized amorphous structure with realistic density, and in which most of the Si atoms have coordination number 4.…”
Section: Methodsmentioning
confidence: 99%
“…Because this method is computationally expensive for large targets, we first constructed a smaller 10×10×10 nm 3 block, and then copied it four times to achieve the desired size. The resulting composite was then annealed with the environment-dependent interatomic potential 32 . This gives an optimized amorphous structure with realistic density, and in which most of the Si atoms have coordination number 4.…”
Section: Methodsmentioning
confidence: 99%
“…The various predicted structures were found to be in excellent structural agreement with microscopy observations and electronic-structure calculations. [2][3][4][5][6][7] Overall, the three different potentials employed, namely, the environment-dependent interatomic potential ͑EDIP͒, 8 Tersoff, 9 and Stillinger-Weber ͑SW͒, 10 all predicted consistent overall trends, leading to a qualitatively coherent picture for some aspects of selfinterstitial clustering in silicon. In particular, it was found that cluster morphology is sensitively dependent on both the temperature and stress within the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The sizes of the cells were chosen to fully enclose the developing cascade within a single cell. The amorphous Si structure was optimized using the algorithm of Wooten, Winer, and Weaire (WWW) [36] and subsequently relaxed using the EDIP. This method gives reasonably optimized amorphous structure with realistic density, where there are almost no coordination defects in the initial structure [37].…”
Section: Simulation Methodsmentioning
confidence: 99%